Editorial: Labour, Migration, and Exploitation during COVID-19 and Lessons (Not) Learnt - Lepp, Annalee; Gerasimov, Borislav (Anti-Trafficking Review, 2023)
This Editorial introduces a Special Issue of Anti-Trafficking Review on COVID-19 and its impacts on labour, migration, and human trafficking. It outlines some of the main challenges that internal and cross-border migrants faced during the pandemic, including closures of workplaces, deportations, lack of access to healthcare and social support, increasing xenophobia and racism, and more. It then presents a summary of the articles contained in the Special Issue and concludes with some broad reflections on the lessons (not) learnt from the pandemic.